2022
DOI: 10.33395/sinkron.v7i1.11203
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration of Profile Matching and MCDM-AHP Methods on Employee Selection for Promotion

Abstract: To give appreciation to every employee who has been able to understand the journey of the system in a company, it is appropriate to be given appreciation in the process of changing leadership and as a form of motivation for all employees in the company as a form of promotion. The promotion process must be carried out objectively, so that a good leadership change system can be seen as a strength in the company's survival for each period. The process of changing leadership through promotions is at the forefront … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
4
0
3
Order By: Relevance
“…Koneksi sosial: gadget memungkinkan anak-anak untuk terus terhubung dengan teman dan keluarga, terutama dalam situasi-situasi di mana pertemuan langsung sulit dilakukan. Media sosial dan aplikasi pesan instan mendukung interaksi sosial (Dewi et al, 2019;Akmaludin et al, 2022).…”
Section: Pendahuluanunclassified
“…Koneksi sosial: gadget memungkinkan anak-anak untuk terus terhubung dengan teman dan keluarga, terutama dalam situasi-situasi di mana pertemuan langsung sulit dilakukan. Media sosial dan aplikasi pesan instan mendukung interaksi sosial (Dewi et al, 2019;Akmaludin et al, 2022).…”
Section: Pendahuluanunclassified
“…The matrix comparison between the criterion values in this study is following the concept of the analytical hierarchy process method with equation (1). Where the criteria value scale is given based on the level of importance of the criteria in The matrix comparison value in Table 7 shows that the GPA obtained criterion has a slightly more important value than the Subject Taken and Repeated subject criteria, while the subject took criteria have an important value that is close to the repeated subject criteria.…”
Section: Build a Comparison Matrixmentioning
confidence: 99%
“…Meanwhile, [20] used file matching to select training instructors. and [21] combined the AHP and profile matching methods to determine the list of the best deans; [22] also combined the AHP and profile matching methods to select students for the Olympics; [23] combined the AHP method and profile matching for employee selection and promotion; and [24] utilized the PROMETHEE method to monitor and evaluate the performance of flight instructors. From the explanation of previous research, it was found that there were various methods used to assist in solving the problem, but determining the important level of each criterion weight on the CPI in previous research was not tested for the value of consistency, so in this study, we used the AHP approach to test consistency and determine the weight of the importance level of each criterion.…”
Section: Introductionmentioning
confidence: 99%